Tutoring, mentoring i coaching w edukacji osób z trudnościami w uczeniu się - Wawrzyniak, Sonia (Studia Edukacyjne, 2020)
Wawrzyniak Sonia, Tutoring, mentoring i coaching w edukacji osób z trudnościami w uczeniu się [Tutoring, Mentoring and Coaching in the Education of People with Learning Difficulties]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 221-234. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.12 The article presents the possibilities it creates using pedagogical innovations such as tutoring, mentoring and coaching supporting the traditional model of education at work with students with school difficulties. Problems withfinding your own path for children and youth, coping skills in a dynamically changing reality,in consumer times with many difficult situations is often undertaken on the basis of school practice and and scientific research. Young people are expected to have knowledge and skills flexible, mobility in various spheres of life because the change is inscribed in the surrounding reality. Important task of modern school and educational institutions is making young people aware of challenges, that stand before them and prepare them to the right life, educational and professional choices in accordance with their capabilities and requirements of the labor market.